Narrative humanism : kindness and complexity in fiction and film. - MOSS-WELLINGTON, WYATT (EDINBURGH UNIV Press, 2020)
This book attempts to clarify the narrative conditions of humanism, asking how we can use stories to complicate our understanding of others, and questioning the ethics and efficacy of attempts to represent human social complexity in fiction.